Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.5812/ijem.74356
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Behavioral Functioning in Mothers of Children with Type 1 Diabetes: Application of Transactional Model of Stress and Coping

Abstract: Background:Having a child with diabetes creates a great deal of stress for mothers. The transactional model of stress and coping is one of the best conceptual frameworks for stressors. Objectives: This study aimed to investigate factors related to health promoting behaviors based on transactional model in mothers of children with type 1 diabetes. Methods: This study was conducted on 180 mothers of children with type 1 diabetes. The data was collected using a multi-sectional questionnaire including demographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Moreover, nonuse of insulin was found to positively predict benign/irrelevant cognitive appraisal in pregnant women with GDM. This was similar to a previous study, which found no significant correlation between use of insulin and negative cognitive appraisal of mothers 43 . A possible explanation was that pregnant women who did not use insulin may generally have milder disease or have relatively easy blood sugar control during pregnancy, with fewer negative experiences associated with blood sugar management 4 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, nonuse of insulin was found to positively predict benign/irrelevant cognitive appraisal in pregnant women with GDM. This was similar to a previous study, which found no significant correlation between use of insulin and negative cognitive appraisal of mothers 43 . A possible explanation was that pregnant women who did not use insulin may generally have milder disease or have relatively easy blood sugar control during pregnancy, with fewer negative experiences associated with blood sugar management 4 .…”
Section: Discussionsupporting
confidence: 89%
“…This was similar to a previous study, which found no significant correlation between use of insulin and negative cognitive appraisal of mothers. 43 A possible explanation was that pregnant women who did not use insulin may generally have milder disease or have relatively easy blood sugar control during pregnancy, with fewer negative experiences associated with blood sugar management. 4 Alternatively, pregnant women using insulin may worry about side effects of insulin treatment and lack knowledge about glucose management and self-care ability, 44 making it difficult to evaluate their health status as benign/irrelevant.…”
Section: Discussionmentioning
confidence: 99%
“…A perception and anticipation of possible harm and threat can significantly impair one’s own mental functions [ 25 , 26 ]. Transactional Theory of Stress and Coping is often the theoretical starting point for the studies of stress in children and their parents/caregivers [ 6 , 27 , 28 , 29 ]. The theory interprets the psychologically stressful experience of parents in the PICU as a result of a complex transaction between the personal characteristics of the parents (e.g., age, gender, level of education, number of children in the family, etc.…”
Section: Methodsmentioning
confidence: 99%
“…Third, contrary to expectations, the present finding demonstrated that OHSS alone did not show a mediating effect on the relationship between DRB and DSE; however, OHCE through OHSS demonstrated a serial mediation effect. Social support positively affected coping outcomes, as indicated by the results of mothers coping with a stressful situation and behavioural function of children with T1D (Asadi Shavaki et al, 2020). In OHC for chronic disease patients, informational and emotional support positively influences individual engagement in OHC, and individual engagement in OHC affects self‐care efficacy (Mirzaei & Esmaeilzadeh, 2021).…”
Section: Discussionmentioning
confidence: 99%